2011
DOI: 10.1007/s11657-011-0064-x
|View full text |Cite
|
Sign up to set email alerts
|

Femoral neck bone mineral density and 10-year absolute fracture risk in a national representative sample of Bulgarian women aged 50 years and older

Abstract: This study is the largest epidemiological osteoporosis trial in Bulgaria to date and allows assumptions about the prevalence of osteoporosis and fractures among women aged 50 and older in our country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 24 publications
(21 reference statements)
1
16
2
Order By: Relevance
“…Bone resorption is a natural phenomenon and can occur due to old age. 12 Osteoporosis affects men and women of any age, more commonly postmenopausal women [12][13][14] and women over 50 years of age 5 . Osteoporosis is more common in women than in men: 50% of women 14 and 25% of men aged over 50 have osteoporotic fractures 15 .…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations
“…Bone resorption is a natural phenomenon and can occur due to old age. 12 Osteoporosis affects men and women of any age, more commonly postmenopausal women [12][13][14] and women over 50 years of age 5 . Osteoporosis is more common in women than in men: 50% of women 14 and 25% of men aged over 50 have osteoporotic fractures 15 .…”
Section: Epidemiologymentioning
confidence: 99%
“…12,16,18 Diseases that are a risk factor for secondary osteo- AIDS, organ transplantation, and liver failure. Medications that cause osteoporosis by reducing the ability of bone to be recovered are: antidepressants, anticonvulsants, antihypertensives, glucocorticoids, diuretics, immunosuppressants, sedatives, tranquilizers, hypoglycemic agents, chemotherapeuticals against excess thyroid hormones.…”
Section: Etiologymentioning
confidence: 99%
See 2 more Smart Citations
“…A study in Bulgaria among women > 50 years found that the mean 10-year absolute fracture risk was 13.4 ± 9.2% (major fractures) and 2.8 ± 5.2% (HP) [17]. A study in Taiwan found that the mean 10-year probabilities of MOF or HF were 13.8% (95% confidence interval (CI) = 10.7%-16.9%) and 2.2% (95% CI = 0.8%-3.5%), respectively [18].…”
Section: Discussionmentioning
confidence: 99%